The Bloomsbury research handbook of Indian aesthetics and the philosophy of art - Chakrabarti, Arindam (Bloomsbury Research Handbooks in Asian Philosophy, 2018)
"The Bloomsbury Research Handbook of Indian Aesthetics and the Philosophy of Art provides an extensive research resource to the burgeoning field of Asian aesthetics. Featuring leading international scholars and teachers whose work defines the field, this unique volume reflects the very best scholarship in creative, analytic, and comparative philosophy. Beginning with a philosophical reconstruction of the classical rasa aesthetics, chapters range from the nature of art-emotions, tones of thinking, and aesthetic education to issues in film-theory and problems of the past versus present. As well as discussing indigenous versus foreign in aesthetic practices, this volume covers North and South Indian performance practices and theories, alongside recent and new themes including the Gandhian aesthetics of surrender and self-control and the aesthetics of touch in the light of the politics of untouchability. With such unparalleled and authoritative coverage, The Bloomsbury Research Handbook of Indian Aesthetics and the Philosophy of Art represents a dynamic map of comparative cross-cultural aesthetics. Bringing together original philosophical research from renowned thinkers, it makes a major contribution to both Eastern and Western contemporary aesthetics"..